How does ICT capital stock affect high-quality economic growth? Evidence from China - Guo, Pengfei; Hu, Zihua; Hu, Xinyun (Technological and Economic Development of Economy, 2025)
As an essential driving force to promote industrial upgrading and technological innovation, ICT has gradually become the technological support for high-quality economic growth. This paper adopts the improved perpetual inventory method and entropy weight TOPSIS method to measure China’s ICT capital stock and economic high-quality growth index, respectively, and experimentally examines the effect of the former on the latter. The findings show that the south has a more extensive ICT capital stock than the north, and the coastal region has a better high-quality growth index than the inland region. Meanwhile, high-quality economic growth, which has increased since 2009 and is incredibly robust in the south, positively correlates with ICT capital stock. Further research finds that ICT capital stock can boost high-quality economic growth by raising marketization and human capital. The results provide policy recommendations for enhancing high-quality economic growth.First published online 19 November 2024